NAVIGATE THE FUTURE OF BUSINESS WITH SUSTAINABLE FINANCIAL STRATEGY - Loso Judijanto; Raden Ayu Trisnayoni; Teguh Wibowo (Jurnal Ekonomi dan Bisnis, 2024)
In a global context that increasingly emphasizes the importance of environmental and social sustainability, face challenges as well as opportunities to redesign their financial strategies. These trends are accelerated by changing consumer preferences, pressure from investors and stakeholders, and tighter regulations on sustainability. The aim of this study is to look further into sustainable financial strategies that can be applied in various business models, and their implementation. The research method used in this study is literature. Research results show that sustainable financial strategies not only minimize negative impacts on the environment and society, but also open access to new capital, enhance brand image, and promote compliance with applicable regulations. Furthermore, the implementation of effective ESG practices has proven to improve the financial performance of companies in the long term. By encouraging a holistic approach that considers external and internal impacts, companies can not only survive but also thrive in a global economy that increasingly demands greater environmental, social, and governance responsibilities.